IMPLEMENTATION OF THE PRINCIPLE OF PROPORTIONALITY IN FINANCIAL TECHNOLOGY–BASED CREDIT AGREEMENTS: A CASE STUDY OF THE SPINJAM PLATFORM - Nurdian, Aria Bagaskara Adi (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
This study investigates the implementation of the principle of proportionality in financial technology based credit agreements through a case study of the SPinjam platform. The research aims to evaluate, first, the formal validity of SPinjam’s electronic agreements under Article 1320 of the Indonesian Civil Code and, second, the substantive fairness of contractual terms viewed through proportionality. A normative juridical method with qualitative analysis is employed, drawing on statutory interpretation of Law No. 11 of 2008 on Electronic Information and Transactions, Government Regulation No. 71 of 2019 on the Implementation of Electronic Systems and Transactions, and OJK Regulation No. 77 of 2016 on information technology based lending and borrowing services. The findings indicate that SPinjam’s electronic consent and signature flows satisfy the four validity requirements of agreement, capacity, a specific object, and a lawful cause. Nevertheless, proportionality is not implemented optimally, particularly in the dimensions of freedom of contract and the distribution of rights and obligations. Standard form clauses that constrain borrower participation and allow unilateral adjustments diminish contractual balance and heighten risk for consumers. The study recommends tighter supervisory measures by the Financial Services Authority to ensure effective disclosure, fair allocation of duties, and proportionate dispute resolution mechanisms. The analysis contributes doctrinal and practical insights for strengthening consumer protection in Indonesia’s digital lending ecosystem.